2016
DOI: 10.1002/jmri.25172
|View full text |Cite
|
Sign up to set email alerts
|

Use of intravoxel incoherent motion MRI to assess renal fibrosis in a rat model of unilateral ureteral obstruction

Abstract: IVIM MRI shows great potential in noninvasive assessment of renal fibrosis induced by UUO. J. Magn. Reson. Imaging 2016;44:698-706.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 29 publications
3
35
0
Order By: Relevance
“…13 IVIM-DWI has been used to detect dysfunction of transplanted kidney in human studies, 14,15 and evaluate renal fibrosis using animal models. [16][17][18] Moreover, cortical D, D*, and f showed a positive correlation with estimated glomerular filtration rate (eGFR) in transplanted kidneys. 14 These studies confirmed the feasibility of IVIM-DWI for the evaluation of renal function and microstructures, and the sclerosis of glomeruli, tubular atrophy, interstitial fibrosis, and interstitial inflammatory cell infiltration in CKD that possibly lead to the reduction of diffusion parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 IVIM-DWI has been used to detect dysfunction of transplanted kidney in human studies, 14,15 and evaluate renal fibrosis using animal models. [16][17][18] Moreover, cortical D, D*, and f showed a positive correlation with estimated glomerular filtration rate (eGFR) in transplanted kidneys. 14 These studies confirmed the feasibility of IVIM-DWI for the evaluation of renal function and microstructures, and the sclerosis of glomeruli, tubular atrophy, interstitial fibrosis, and interstitial inflammatory cell infiltration in CKD that possibly lead to the reduction of diffusion parameters.…”
mentioning
confidence: 99%
“…IVIM‐DWI is able to determine the pure molecule diffusion by calculating the diffusion coefficient of nonperfusion‐based molecular diffusion (D), and evaluate intravoxel capillary perfusion by calculating the diffusion coefficient of perfusion‐based molecular diffusion (D*), as well as the perfusion fraction (f) . IVIM‐DWI has been used to detect dysfunction of transplanted kidney in human studies, and evaluate renal fibrosis using animal models . Moreover, cortical D, D*, and f showed a positive correlation with estimated glomerular filtration rate (eGFR) in transplanted kidneys …”
mentioning
confidence: 99%
“…The UUO model has been widely employed in the study of renal fibrosis, especially for radiological research . However, UUO‐induced renal fibrosis is different from the clinical scenario, as complete acute obstruction can be promptly relieved through surgical intervention in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The blunt dissection of the left ureter was followed by double ligation of the lower ureter. Next, the abdominal cavity was closed . Five days after the surgery, 24 of the rats had obstructed ureters reimplanted into their bladders.…”
Section: Methodsmentioning
confidence: 99%
“…An attractive characteristic compared with other imaging modalities is the ability to combine 1 H and 13 C MRI for multiple measures of both anatomy and function. For example, a comprehensive assessment of the kidney may also include renal fibrosis measurements using diffusion‐weighted MRI or T 1 mapping . Combined imaging of metabolism by hyperpolarized 13 C MRI with proton methods could yield important information about the possible interplay and timing between metabolic changes, inflammation and fibrosis that could help to guide the utility of functional MRI of the kidney as a means to monitor renal disease severity and progression …”
Section: Discussionmentioning
confidence: 99%